Electromagnetic radiation concerning human health and environmental issues - KOPET, EVELYN BLINDA (Universiti Malaysia Sarawak (UNIMAS), 2002)
THis project focuses on the possible electromagnetic (EM) radiation risks, based on some simple experiments conducted in the laboratory.